REVIEW ON HARD SEGMENT INFLUENCESON THE PHYSICALPROPERTIES OF THERMOPLASTICPOLYURETHANES - Nurul Hidayati Fithriyah (JURNAL KONVERSI, 2012)
Thermoplastic polyurethanes (TPUs) are the fastest growing market in polyurethane technology mainly due to their easy process ability, versatile properties and recyclable nature. They find applications in high performance materials like coatings, adhesives, fibres and foams in a variety of industries ranging from automotive and footwear to medical implants. TPUs are linear block copolymers comprising of alternating soft and hard segments. The versatile properties of TPUs are usually attributed to their phase-separated morphologies. Different parameters are known to affect TPUs physical properties. One of those is their chemical architecture that is the statistical arrangement of hard segments (HS) and soft segments (SS).In particular the architecture of the HS will influence the molecular structure and intermolecular interaction. Its role as physical crosslink sites will govern thermal, mechanical and morphological properties. Hence a modification of HS chemical architecture might adjust the ultimate properties of TPU. This implication is important in process control of production and design of application. Therefore this paper will review various studies to understand the effect of different architecture to the properties of TPU. Keywords: thermoplasticpolyurethanes, hard segment architecture, physical properties